2018
DOI: 10.3390/environments5060067
|View full text |Cite
|
Sign up to set email alerts
|

Linking Marine Ecosystem Services to the North Sea’s Energy Fields in Transnational Marine Spatial Planning

Abstract: Marine spatial planning temporally and spatially allocates marine resources to different users. The ecosystem approach aims at optimising the social and economic benefits people derive from marine resources while preserving the ecosystem’s health. Marine ecosystem services are defined as the benefits people obtain from marine ecosystems. The aim of this study is to determine which interrelations between marine ecosystem services and the marine energy industry can be identified for use in transnational marine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…For instance, studies that focus on specific compartments of the ecosystem rather than the full range of affected structures and processes, e.g. changes in epibenthic community due to OWF [36,60]; or studies that provide a holistic overview of the services affected by OWFs but only identify impacts and do not describe pathways supplying ES [32,[39][40][41]. Studies that represent the pathways from the human impacts to ES supply are often qualitative and expert-based [31,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, studies that focus on specific compartments of the ecosystem rather than the full range of affected structures and processes, e.g. changes in epibenthic community due to OWF [36,60]; or studies that provide a holistic overview of the services affected by OWFs but only identify impacts and do not describe pathways supplying ES [32,[39][40][41]. Studies that represent the pathways from the human impacts to ES supply are often qualitative and expert-based [31,42].…”
Section: Discussionmentioning
confidence: 99%
“… References Provisioning Cultivated aquatic plants for nutrition, materials or energy Plants cultivated by in-situ aquaculture grown for nutritional purposes Farmed aquatic plants (for food, materials and energy) Causon & Gill, 2018 [ 36 ]; UNITED project (Offshore Wind and Flat Oyster Aquaculture & Restoration in Belgium, n.d.) [ 37 ] Fibers and other materials from in-situ aquaculture for direct use or processing (excluding genetic materials) No Plants cultivated by in-situ aquaculture grown as an energy source Reared aquatic animals for nutrition, materials or energy Animals reared by in-situ aquaculture for nutritional purposes Farmed aquatic animals (for food, materials and energy) Causon & Gill, 2018 [ 36 ]; UNITED project (Offshore Wind and Flat Oyster Aquaculture & Restoration in Belgium, n.d.) [ 37 ]; EDULIS project (Offshore Mussel culture in Wind Farms | BLUEGENT, n.d.) [ 38 ] Fibers and other materials from animals grown by in-situ aquaculture for direct use or processing (excluding genetic materials) Yes Animals reared by in-situ aquaculture as an energy source Wild animals (terrestrial and aquatic) for nutrition, materials or energy Wild animals (terrestrial and aquatic) used for nutritional purposes Wild aquatic animals (for food, materials and energy) Causon & Gill, 2018 [ 36 ]; Vogel et al, 2018 [ 39 ]; Hooper et al, 2017 [ 40 ]; Busch et al, 2011 [ 41 ]; Papathanasopoulou et al, 2015 [ 42 ] Fibers and other materials from wild animals for direct use or processing (excluding genetic materials) Yes Wild animals (terrestrial and aquatic) used as a source of energy Mineral substances used for nutrition, materials or energy Mineral substances used for material purposes Sand and other minerals …”
Section: Case Study Applicationmentioning
confidence: 99%
“…Only one scientific publication was found that established a direct link between marine uses and ES supply. Vogel et al (2018) analysed the relationships between marine ES supply and the energy industry sector in the North Sea. Based on their research it was possible to assess ES supply in relation to the marine uses "offshore wind turbines" with a high confidence (confidence value 3).…”
Section: Literature-based Matrixmentioning
confidence: 99%
“…Up until now, research concerning the interrelations between uses and the supply of ES in the marine context is insufficient. With regard to the case study area, Vogel et al (2018) demonstrated the links of 23 ES to seven offshore energy sources in the wider North Sea region. The results reveal clear positive and negative interactions within the studied linkages.…”
Section: Marine Ecosystem Services Supply In the German Baltic And No...mentioning
confidence: 99%